Antiapoptotic Properties of Mesenchymal Stem Cells in a Mouse Model of Corneal Inflammation - Kossl, Jan; Bohacova, Pavla; Hermankova, Barbora; Javorkova, Eliska; Zajicova, Alena; Holan, Vladimir (Stem cells and development, 2021)
Mesenchymal stem cells (MSCs) represent a population of adult stem cells that have potent immunoregulatory, anti-inflammatory, and antiapoptotic properties. In addition, they have ability to migrate to the site of inflammation or injury, where they contribute to the regeneration and healing process. For these properties, MSCs have been used as therapeutic cells in several models, including treatment of damages or disorders of the ocular surface. If the damage of the ocular surface is extensive and involves a limbal region where limbal stem cell reside, MSC therapy has been proved as the effective treatment approach. Although the anti-inflammatory properties of MSCs have been well characterized, mechanisms of antiapoptotic action of MSCs are not well recognized. Using a chemically damaged cornea in a mouse model, we showed that the injury decreases expression of the gene for antiapoptotic molecule Bcl-2 and increases the expression of proapoptotic genes Bax and p53. These changes were attenuated by local transplantation of MSCs after corneal damage. The antiapoptotic effect of MSCs was tested in an in vitro model of co-cultivation of corneal explants with MSCs. The apoptosis of corneal cells in the explants was induced by proinflammatory cytokines and was significantly inhibited in the presence of MSCs. The antiapoptotic effect of MSCs was mediated by paracrine action, as confirmed by separation of the explants in inserts or by supernatants from MSCs. In addition, MSCs decreased the expression of genes for the molecules associated with endoplasmic reticulum stress Atf4, Bip, and p21, which are associated with apoptosis. The results show that MSCs inhibit the expression of proapoptotic genes and decrease the number of apoptotic cells in the damaged corneas, and this action might be one of the mechanisms of the therapeutic action of MSCs.
Keywords: Gene Expression Regulation; modely nemocí na zvířatech; mouse model; rohovka; cyklooxygenasa 2; cytokiny; myši inbrední BALB C; Keratitis; Mesenchymal Stem Cell Transplantation; Bcl-2; Corneal Injuries; polymerázová řetězová reakce s reverzní transkripcí; cornea; Mice, Inbred BALB C; keratitida; mesenchymal stem cells; kultivované buňky; Animals; lidé; ženské pohlaví; Humans; antiapoptotic properties; zvířata; regulace genové exprese; Disease Models, Animal; Reverse Transcriptase Polymerase Chain Reaction; myši; apoptóza; Cyclooxygenase 2; poranění rohovky; Cells, Cultured; Cytokines; hepatocytární růstový faktor; Mice; Female; transplantace mezenchymálních kmenových buněk; Bax; Mesenchymal Stem Cells; Hepatocyte Growth Factor; Cornea; Apoptosis; mezenchymální kmenové buňky